2022
DOI: 10.3390/molecules27041381
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cell-Potent and Selective Peptidomimetic Inhibitors of Protein N-Terminal Methyltransferase 1

Abstract: Protein N-terminal methyltransferase 1 (NTMT1) recognizes a unique N-terminal X-P-K/R motif (X represents any amino acid other than D/E) and transfers 1–3 methyl groups to the N-terminal region of its substrates. Guided by the co-crystal structures of NTMT1 in complex with the previously reported peptidomimetic inhibitor DC113, we designed and synthesized a series of new peptidomimetic inhibitors. Through a focused optimization of DC113, we discovered a new cell-potent peptidomimetic inhibitor GD562 (IC50 = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Compound 3 was synthesized by following our previously reported method. 26 4.1.4. (S)-Piperidin-3-yl (2-(2-(4-Fluorophenyl)thiazol-4-yl)propan-2-yl)carbamate (4).…”
Section: (S)-quinuclidin-3-yl (2-(2-(4-fluorophenyl)thiazol-4-yl)prop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 3 was synthesized by following our previously reported method. 26 4.1.4. (S)-Piperidin-3-yl (2-(2-(4-Fluorophenyl)thiazol-4-yl)propan-2-yl)carbamate (4).…”
Section: (S)-quinuclidin-3-yl (2-(2-(4-fluorophenyl)thiazol-4-yl)prop...mentioning
confidence: 99%
“…Different approaches have been applied to discover cell-potent NTMT1/2 inhibitors as chemical probes to dissect their biological function (Figure ). Among them, bisubstrate inhibitors selectively inhibit recombinant NTMT1 at 140 pM but are impermeable to cell membranes. Compared to bisubstrate inhibitors, peptidomimetic inhibitors inhibit both NTMT1 and 2 (NTMT1/2), displaying modest cellular potency in the micromolar range. Following up on our recent discovery of venglustat as the first cell-potent and small-molecule inhibitor of NTMT1 (Figure ), we describe here our efforts to systematically examine the structure–activity relationship (SAR) of venglustat to boost its potency and selectivity, as well as demonstrating its applicability for inhibiting Nα methylation that is catalyzed by NTMT1/2.…”
Section: Introductionmentioning
confidence: 99%
“…5 ). A recent study reported the development of a novel inhibitor in this class, GD562, which improves the inhibition of cellular N-terminal methylation by 6-fold compared with DC541 ( 118 ). Overall, NTMT1 inhibitors have steadily improved in cell potency and are staged to be further employed for mechanistic and cellular studies.…”
Section: Tools For Studying Protein να Mtasesmentioning
confidence: 99%
“…Although there are potent and selective NTMT1 bisubstrate inhibitors, their intrinsic properties restrict them for cell-based studies. Meanwhile, selective peptidomimetic inhibitors only exhibited modest cellular inhibition with an IC 50 ≈ 50 μM. Therefore, cell-active small-molecule inhibitors of NTMT1 are in demand. Here, we report the identification of venglustat as a cell-potent inhibitor of NTMT1 resulting from a quantitative high-throughput screening (qHTS).…”
Section: Introductionmentioning
confidence: 99%